Three-dimensional fatigue crack growth prediction method based on consistency retention. (December 2022) - Fang, Xin; Liu, Guijie; Wang, Honghui; Xie, Yingchun; Tian, Xiaojie; Leng, Dingxin; Mu, Weilei; Ma, Penglei; Li, Gongbo
Graphical abstract: Highlights: A 3D crack growth update method considering load sequence effect based on XFEM is proposed. The consistency retention strategy for crack growth life and path is proposed. A framework for 3D fatigue crack growth based on consistency retention is built. From 2D crack growth to 3D crack growth, the effectiveness of the proposed method is verified. The proposed method can achieve dynamic following and accurate prediction of 3D fatigue crack growth. Abstract: To reduce the influence of uncertain factors, a three-dimensional fatigue crack growth prediction method based on consistency maintenance is proposed. Firstly, the crack growth update under complex loads is realized based on XFEM. Subsequently, the life correction method based on the improved particle filter and the path correction method based on the improved maximum tangential stress criterion are proposed. Taking real crack data as input, the accuracy of prediction results is improved from two dimensions of life and path. Finally, five cases are used to verify the proposed framework, which proves that it can realize dynamic tracking of crack growth.